PENGARUH SPESIALISASI KEAHLIAN KAP TERHADAP TAX AVOIDANCE ( STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI ) - Eka Setiyawati; Abdul Rohman (Diponegoro Journal of Accounting, 2015)
The objective of this study is to analyze the influence of  Specialization KAP Expertise on Extent Tax Avoidance. The analysis used two independent variable such as  Tax Expert and Over all Expert. Over all Expert i.e. the combined tax and audit expert.  The dependent variable is Tax Avoidance.The sample used in this study was the secondary data from Bursa Efek Indonesia ( Indonesian Stock Exchange), i.e. the annual report of financial company listed in BEI for the year 2011-2013. The sample was taken using the purposive sampling method. The total number samples in this study consists of 226 firms.The statistics method used in this study was multiplied linear refression annalysis, the hypotheses testing used statistic F and t tests, and determinant coefficient. The analysis showed that Tax Expert and Over all Expert had significant influences on Tax Avoidance.